Power in Practice: Trade union education in Sierra Leone - Stirling, John (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2013)
This article presents an analysis of the development of a trade union education program in Sierra Leone in the geo-historical context of British colonialism. It places the argument in relation to the contradictory trends of trade unionism more generally and alongside their antagonistic cooperation with capitalism. It discusses the limits and potentialities of a radical pedagogy when trade unions are constrained to engage with existing power structures that use English as the dominant language. It places more theoretical arguments within the context of a country characterized by major inequalities and facing the neo-liberal challenges of globalization and a trade union movement seeking to be representative of an informal workforce but rooted in the formal economy.